Receptive fields of motor neurons underlying local tactile reflexes in the locust - Siegler, MV (J Neurosci, 1986)
The receptive fields of motor neurons to a hind leg were mapped by recording intracellularly from their cell bodies or from the muscle fibers they innervate while stimulating mechanoreceptors on the surface of that leg. Each motor neuron is affected by a specific array of receptors that make up its receptive field. Boundaries along the anteroposterior or dorsoventral axes of the leg divide the receptive fields into excitatory and inhibitory regions. Proximodistal boundaries may correspond to the articulations between parts of the leg. Motor neurons that innervate antagonistic muscles have complementary receptive fields, so that the region that is excitatory for one is inhibitory for the other. The receptive fields of the motor neurons overlap. Tactile stimulation therefore leads to a specific local reflex that involves the coordinated movement of the segments of a leg. Five local reflexes are described, each of which moves the leg away from the site of stimulation. Afferents from the external mechanoreceptors do not synapse directly on the motor neurons, but instead on spiking local interneurons, some of which then synapse directly on motor neurons. These local interneurons have smaller receptive fields delineated by the same boundaries, so that the receptive fields of the motor neurons can be constructed from appropriate combinations of them. It is suggested that receptive fields are organized as “functional maps” that are appropriate for particular behavioral responses rather than solely to preserve or refine spatial information.